Improving Population Administration Services through the Implementation of the “Dimana Anda Kemana Anda Kami Layani” Program (Dinda Kanda Kalayani) by the Population and Civil Registration Office of Ngawi District - Ro’uf, Muhammad Mufid; Reviandani, Oktarizka (Formosa Journal of Multidisciplinary Research, 2024)
Administrative services, especially population administration, are one of the important aspects of public services. Population administration includes managing population data, making and issuing population documents such as identity cards (KTP-el), family cards (KK), birth certificates, and other important documents. Local governments are required to be more responsive and creative in improving the quality of services to the community. Therefore, the Ngawi Regency Population and Civil Registration Office implemented the “Dimana Anda Kemana Anda Kami Layani” (DINDA KANDA KALAYANI) program in improving population administration services. This research uses qualitative research with a case study approach. Data collection techniques are interviews, observation and documentation. By using the theory of George Charles Edwards III's implementation approach. The results showed that 1) Communication has gone well with various related parties, such as the sub-district government, villages, schools, and event organizers, 2) Resources provided are adequate, 3) Disposition has been carried out by officers who are members of the basic proactive outreach service team understanding the basis of existing regulations and guidelines, and 4) Bureaucratic Structure has implemented SOP’s in accordance with applicable regulations.